Nitrogen Stimulates the Growth of Subsurface Basalt-associated Microorganisms at the Western Flank of the Mid-Atlantic Ridge - Zhang, Xinxu; Fang, Jing; Bach, Wolfgang; Edwards, Katrina J.; Orcutt, Beth N.; Wang, Fengping (Frontiers in Microbiology, 2016)
Oceanic crust constitutes the largest aquifer system on Earth, and microbial activity in this environment has been inferred from various geochemical analyses. However, empirical documentation of microbial activity from subsurface basalts is still lacking, particularly in the cool (<25 °C) regions of the crust, where are assumed to harbor active iron-oxidizing microbial communities. To test this hypothesis, we report the enrichment and isolation of crust-associated microorganisms from North Pond, a site of relatively young and cold basaltic basement on the western flank of the Mid-Atlantic Ridge that was sampled during Expedition 336 of the Integrated Ocean Drilling Program. Enrichment experiments with different carbon (bicarbonate, acetate, methane) and nitrogen (nitrate and ammonium) sources revealed significant cell growth (one magnitude higher cell abundance), higher intracellular DNA content, and increased Fe3+/ΣFe ratios only when nitrogen substrates were added. Furthermore, a Marinobacter strain with neutrophilic iron-oxidizing capabilities was isolated from the basalt. This work reveals that basalt-associated microorganisms at North Pond had the potential for activity and that microbial growth could be stimulated by in vitro nitrogen addition. Furthermore, iron oxidation is supported as an important process for microbial communities in subsurface basalts from young and cool ridge flank basement.